Utility of thromboelastography for the diagnosis of von Willebrand disease. Issue 7 (4th April 2019) - Regling, Katherine; Kakulavarapu, Srikruthi; Thomas, Ronald; Hollon, Wendy; Chitlur, Meera B.
Abstract: Von Willebrand disease (VWD) is an inherited bleeding disorder that is caused by a quantitative or qualitative deficiency of von Willebrand factor (VWF). The National Heart, Lung, and Blood Institute (NHLBI) guidelines for the diagnosis of VWD state that a VWF activity (VWF:RCo) of <30 IU/dL or <50 IU/dL with symptoms of clinical bleeding are consistent with the diagnosis of VWD. However, current gold‐standard diagnostic testing takes days to have complete results. Thromboelastography (TEG) is a testing method that provides a graphical trace that represents the viscoelastic changes seen with fibrin polymerization in whole blood, therefore providing information on all phases of the coagulation process. This study describes the TEG characteristics in 160 patients who presented for workup of a bleeding disorder and a subset of those were subsequently diagnosed with VWD. The TEG parameters, K‐time (representing the dynamics of clot formation) and the maximal rate of thrombus generation (MRTG), were found to be sensitive in detecting patients with VWF:RCo <30 IU/dL. The TEG, unlike VWF:RCo, can be done in real time, and results are available to the clinician within an hour. This will definitely be beneficial in acute situations such as evaluation of and management of acute bleeding in patients with acquired deficiencies of VWF and may play an important role in the surgical management of patients with VWD.